2020
DOI: 10.1080/07391102.2020.1840439
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the initiation and termination codons of SARS-CoV-2 spike protein as possible therapy against COVID-19: the role of novel harpagide 5-O-β-D-glucopyranoside from Clerodendrum volubile P Beauv. (Labiatae)

Abstract: The global spread of the coronavirus infections disease − 2019 (COVID-19) and the search for new drugs from natural products particularly from plants are receiving much attention recently. In this study, the therapeutic potential of a new iridoid glycoside isolated from the leaves of Clerodendrum volubile against COVID-19 was investigated. Harpagide 5-O-β-D-glucopyranoside (HG) was isolated, characterised and investigated for its druglikeness, optimized geometry, and pharmacokinetics pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Cytokine storms have been implicated in the pathophysiology of COVID-19 infection and its complications. This is depicted by exacerbated cellular levels of proinflammatory cytokines such as TNF-α, IL-2 and IL-7 [ [6] , [7] , [8] ]. ORF8 has been reported to play a major role in SARS-CoV-2 induction of cytokine storms in COVID-19 [ 16 , 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cytokine storms have been implicated in the pathophysiology of COVID-19 infection and its complications. This is depicted by exacerbated cellular levels of proinflammatory cytokines such as TNF-α, IL-2 and IL-7 [ [6] , [7] , [8] ]. ORF8 has been reported to play a major role in SARS-CoV-2 induction of cytokine storms in COVID-19 [ 16 , 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…SARS-CoV-2 has been reported to cause infection by triggering an excessive immune response depicted by aggravated levels of macrophage inflammatory protein 1-α, tumour necrosis factor-α (TNF-α), interleukins (IL)-2 and −7, monocyte chemoattractant protein 1, and granulocyte colony stimulating factor [ [6] , [7] , [8] ]. This process is regarded as cytokine storm and has been implicated in the pathology and severity of COVID-19 and its mortality [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the use of supplements that can boost the host immune system has been documented as a good strategy to fight the virus [ 85 ]. Unfortunately, research on the exploration of medicinal plants for the development of antiviral drugs against coronavirus is slow, as much attention has been currently geared towards vaccine development globally [ 86 , 87 ]. Erukainure and colleagues [ 86 ] have investigated the inhibitory potential of harpagide 5- O -β-D-glucopyranoside, a new iridoid glycoside isolated from methanolic leaves of C. volubile against SARS CoV-2.…”
Section: Pharmacological Potentials Of C Volubilementioning
confidence: 99%
“…Several studies have reported the potentials of medicinal plants in the treatment and management of COVID-19 and its complications (Benarba and Pandiella, 2020;Erukainure et al, 2020;Vellingiri et al, 2020). These therapeutic properties have been attributed to the phytochemical constituents of the plants.…”
Section: Introductionmentioning
confidence: 99%